Periodontal disease as a primary cause of surgical site infection in fractures of the mandible: is smoking a confounding variable?. Issue 10 (December 2022) - Janaphan, K.; Hashem, I.; Smith, C.; Holmes, S.; Chatzopoulou, D.
Abstract: Fractures of the mandible are common in contemporary oral and maxillofacial practice. Wound infection is the most common complication after open reduction and internal fixation, and the management of these is complex and costly in terms of morbidity to the patient, and in fiscal terms. Whilst numerous epidemiological studies implicate smoking, alcohol, drug use, and adverse behaviour, as well as fracture complexity and diabetes, as important risk factors, the role of periodontal disease is only occasionally mentioned and not formally investigated. The aim of this study therefore was to assess the presence of periodontal disease and its severity according to the 2018 EFP/AAP periodontitis case classification in patients with fractured mandibles who presented to a single level 1 trauma centre, and to look for a possible association with surgical site infection. A total of 305 patients were assessed retrospectively following open reduction and internal fixation via transoral incisions with load-sharing osteosynthesis. The postoperative infection rate was 22.95%. Multivariate and multiple logistic regression revealed that there was a strong association between periodontal staging and postoperative surgical site infection. Crucially, the study predicts that patients with severe periodontal disease (periodontal stage III and IV) are over seven times more likely to develop a wound infection than disease-negative individuals. This has implications for risk adjustment, prognostication, treatment planning, and postoperative care. Surprisingly in this study, cigarette smoking, an established risk factor in the pathogenesis of periodontal disease, did not achieve statistical significance, potentially conflicting with the established literature.